(3fgGjI GdCMcGe aj eYQaI GdGMcGes - (3GdMdj, CHh efUhQ, GHf GdeWgQ, LeGd GdOjf, GdMSf Hf jhSa Hf Ydj GHf GdeWgQ, J (B726(3g`s ((3YHO Gddg Hf eMeO Hf Ydj GdTQhJjs)
(3ChdgG (B:s
(3GdMeO ddg (B... (3cJGH GdWgGQI (B... (3jchf aj UfOhb ajg beGT ajMedg hdGeS LdO GdeUMa dCfg XQa hhYGA deG cJH Ydjg GdbQBf bCTHg cjSg hdG aj eS GdMhGTj hdG GdHjGV NdGd GdSWhQ NdGd GdSWhQ deSGhGJg ZjQg (B...s
(3BNQgG (B:s
... (3a dCf aGWeI YdjgG GdSdGe cGfJ JCJj bHhQ GdTgOGA aj ZOGI cd SHJ aJCJj bHQ MeRI Ydjg GdSdGe hJJQMe Ydjg hJSJZaQ dg , Jes
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B2/ 227s
(3GdPQjYI (B24 ( 2108 )s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis